A fluorescent colorimetric azo dye based chemosensor for detection of S2− in perfect aqueous solution and its application in real sample analysis and building a molecular logic gate. Issue 20 (24th April 2018) - Manna, Amit Kumar; Mondal, Jahangir; Chandra, Rukmani; Rout, Kalyani; Patra, Goutam Kumar
Abstract : A fluorescent-colorimetric azo dye based bis -Schiff base chemosensor, L, has been developed.L can selectively detect S 2− through a color change from yellow to orange in perfect aqueous solution by deprotonation mechanism. Abstract : A simple azo -dye based bis -Schiff base chemosensor, L, has been designed, synthesized and characterized by NMR and IR spectroscopy, ESI-MS and elemental analysis. The chemosensorL can successfully detect sulfide ions both visually and spectro-photometrically in perfect aqueous medium as well as in an organic–aqueous mixture through a de-protonation mechanism. The detection limit reaches 16 μM in pure aqueous medium (1.7 μM by UV-vis titration and 3.35 × 10 −7 M by fluorescence titration in a 1 : 1 DMSO–H2 O mixture), which is the lowest detection limit ever reported in the family of Schiff base chemosensors for sulfide ions. Other interfering anions (F −, Cl −, Br −, HSO3 −, N3 −, PO4 3−, NO3 −, OAc −, CO3 2− and CN − ) exhibited no interference for the detection of sulfide ions. The mechanism of interaction betweenL and sulphide ions has further been confirmed by DFT studies. The chemosensorL has also been applied for real sample analysis and in building a molecular logic gate.